Comparative outcome analysis of ABO-incompatible and positive crossmatch renal transplantation: a single-center experience - Padmanabhan, Anand; Ratner, Lloyd E; Jhang, Jeffrey S; Duong, Jimmy K; Markowitz, Glen S; Vasilescu, Elena R; Crew, Russell J; Schwartz, Joseph (Transplantation, 2009)
ABO-incompatible (ABOi) and positive crossmatch (XM) renal transplants pose special immunologic challenges. It is important to compare outcomes, study resource utilization, and attempt to risk stratify patients in these higher risk transplant settings. We compared apheresis utilization and transplant outcomes in ABOi, XM, and combined ABOi-XM renal transplants. We also analyzed multiple parameters, including patient and laboratory variables, to identify predictors of transplant outcome. Incidences of early (< or =30 days posttransplant) antibody-mediated rejection (AMR) and acute cellular rejection (ACR) were similar among the three incompatible groups whereas they differed in allograft rejection for late (>30 days posttransplant) AMR and ACR. Notably, there were no episodes of late AMR among ABOi patients. Patients treated with more than four pretransplant plasmapheresis/intravenous immunoglobulin (PP/IVIg) had a greater likelihood of experiencing early AMR. The median number of posttransplant PP/IVIg treatments was greater than twofold higher in ABOi-XM and XM patients compared to ABOi patients. Patients who required more than five posttransplant PP/IVIg procedures and those with one or more prior renal transplants had higher incidences of late ACR. Our analysis aids in defining apheresis resource utilization and helps in risk stratification of incompatible renal transplantation. It also aids in predicting allograft rejection and provides an opportunity for preemptive monitoring and treatment.